A Generic Model for Predicting the Permeability of Fiber Mats - Dong, Chensong; Tang, Tuong (Trans Tech Publications Inc, 2010)
A new empirical model for predicting the permeability of fiber mats is presented in this paper. Permeability data were collected from the NIST reinforcement permeability database and categorized according to the material architecture. It is seen from the data that for each category, permeability is proportional to fiber volume fraction. In order to describe the behavior of permeability vs. fiber volume fraction, the location, scale and shape parameters were introduced for each material category. The model was validated against the experimental data and good agreement was found.